A Mimicker of Gallbladder Carcinoma: Cystic Gastric Heterotopia with Intestinal Metaplasia - Gonca ÖZGÜN; Şaduman BALABAN ADIM; Nesrin UĞRAŞ; Sadık KILIÇTURGAY (Federation of Turkish Pathology Societies, 2017)
Heterotopic gastric mucosa in the gallbladder is an unusual entity and is usually clinically silent. We report a 75-year-old female patient who presented with intermittent upper abdomial pain radiating to the back. Abdominal imaging studies showed a sessile polypoid lesion and a gallstone in the gallbladder. Gallbladder carcinoma was suspected and cholecystectomy performed. Intraoperative frozen section examination suggested mucinous tumor, suspicious for malignancy. However, the permanent sections revealed aberrant gastric tissue consisted of gastric pyloric and fundic glands of heterotopic gastric mucosa with intestinal metaplasia in the gallbladder.